Analisis Semiotika pada Film Damsel Menurut Teori Charles Sanders Pierce - Deniela Yoshelyn S.; Efani Margareth G.; Grace Fanesya G.; Nurul Nabila L.; Salsabil Putri; Tri Indah Prasasti (Journal on Education, 2024)
This article discusses the analysis of semiotic theory according to Charles Sanders Pierce contained in the film "Damsel". This film shows complexity in symbols such as icons, indexes, and symbols, which mark important messages in the story. Through qualitative descriptive methods, this research examines three types of signs in the film: the visual icon of the dragon, the index of the tragedy experienced by the women who are victims, and the symbol of Elodie's actual marriage to Henry as a political strategy. The results of the discussion reveal hidden messages in each scene, providing new insight into courage and justice in the story "Damsel".